THE SUBJECTIVE PORTRAYAL OF PUBLIC FIGURES:A CRITICAL ANALYSIS OF OBAMA AND MCCAIN'S ELECTIONIN NEWSPAPER COLUMNS - Juis Marlina, - (2009)
This research entitles "THE SUBJECTIVE PORTRAYAL OF PUBLIC FIGURES: A CRITICAL ANALYSIS OF OBAMA AND MCCAIN'S ELECTION IN A NEWSPAPER COLUMN". The aims of the study are to discover the ideologies beneath the US presidential election in a news website by analyzing critically Scoblete's political texts, which were taken from www.realclearpolitics.com, and to reveal any hidden meanings or the representation of certain ideology presented linguistically in the news websites concerning the political issues. This paper analysis employs a qualitative method. Critical discourse analysis (CDA) was used to analyze the texts by focusing on the linguistic analysis by Fairclough, the analysis processes of CDA by Halliday (transitivity), and the use of agenda-setting theory related to the study by McComb. The study shows that transitivity and agenda-setting theory can be elaborated and used as a basis for examining the position of Scoblete's articles on the political issues in the US election through the portrayal of the opponent of John McCain in more negative ways. It was proved by 14 sentences which seemed to take sides with this Republican's candidate, while there were only two sentences taking sides to his opponent. It reveals that the author attempted to influence and convince the public that McCain has better and more sensible ideas than his opponent, Barack Obama. This negative portrayal by the author, however, did not seem to work well since Obama was finally elected as the president of US